A Discussion on Yin-Yang, Zhong-Yong, Ambidexterity, and Paradox - Xin Li (Copenhagen Business School (CBS), Asia Research Community (ARC), 2019)
Professor Peter Ping Li has made important contribution to the promotion of indigenous management research in China in general and application of Chinese Yin-Yang philosophy to organizational paradox research in particular. However, his interpretation of Yin-Yang is incomplete and inaccurate. Namely, his notion of Yin-Yang balancing relates to only one of five distinct epistemological expressions of Yin-Yang in the Chinese literature and its derived methodological prescription, i.e., Confucian principle of Zhong-Yong. Yet, his notion of Yin-Yang balancing is an inaccurate representation of Zhong-Yong due to his dogmatic insistence on asymmetry in the structure of combination of opposites that is not a prescription of the Zhong-Yong principle. Due to his incomplete understanding of Yin-Yang, he has not been able to see the value of the ambidexterity approach and its compatibility with the Yin-Yang thinking in particular and the similarity between Chinese and Western approaches to solving paradox in general. This paper alerts Chinese management scholars to the danger of overconfidence and Chinese exceptionalism and calls for a modest and prudent attitude in pursuing Chinese indigenous management research.
hdl:10398/9703
Keywords: 330; Yin-Yang; Zhong-Yong; Paradox; Ambidexterity; Indigenous; China